Addressing Supply-Side Hurdles to Gender-Equal Representation in Germany - Davidson-Schmich, Louise K. (My University, 2018)
One hundred years after being granted the right to active suffrage, German women remain underrepresented in elective office. Quotas have partially addressed demand-side barriers to gender parity in descriptive representation, but significant supply-side gaps remain. Men comprise over 70% of political party members in the Federal Republic, dominating the bodies that provide candidates for elective office. Solutions to this supply-side problem have often focused on “fixing” women to fit into gendered party institutions, rather than altering these structures to be more welcoming to women. In contrast, drawing on interviews with (potential) party members in Germany, this article identifies informal institutions that deter gender-balanced involvement in political parties and suggests ways in which these norms might be changed.
Keywords: Partizipation; political parties; Politik; Repräsentation; underrepresentation; ddc:300 Sozialwissenschaften; ddc:300